1087 Establishing Guidelines for VTE Prophylaxis for Acute ENT Admissions. (12th October 2021) - Wallace, J; Hepburn, K; O'Hanlon, J; Davis, S
Abstract: Aim: VTE prophylaxis is a vital aspect of patient safety. The decision whether to offer pharmacological thromboprophylaxis is a balance of risk versus benefit. There is a low incidence of VTE in ENT patients, admissions are often short and active bleeding on admission is not uncommon (epistaxis patients, already on anticoagulation are particularly difficult to manage